Upaya Meningkatkan Sosialisasi Dengan Melatih Cara Berkenalan Pada Klien Isolasi Sosial: Menarik Diri - Aji, Raka Prihutomo; , Arif Widodo, A.Kep., M.Kes (2017)
Beground: From years to years in the world people with mental disorder or skizofrenea happen incrase according to World Health Organization (WHO) in 2013 there are lot of significant increase in 2013 there are 450 milion people with mental disorder and will be increase 15 % in 2030. Mental disorder is a condition where the disturbance Process of the mine Disorders Process Thought iki will cause gaps in the communities that will have an impact on individuals who were or ever experience mental disorder reluctant to review Socialize with society which led to social isolation, social isolation is negative symptoms from mental disorders. That social isolation situation where someone not willing or not able to review other people because of any factor from the inside or from the outside.Aim of Research: For give nursing care to the clien with social isolation in Sena room RSJ Surakarta with dray include assessment, intervention, implementation, and evaluationMethod: The Author use discriptive method with study of the case for 4x 24 hours in RSJD Arief Zainudin Surakarta.Result: Clien can knowing cause social isolation, profit if can get interaction with other people, how to get acquainted with nurse and acquainted with other people in nursing room , join with activity group.Consclusion: Success of the terapeutic communication to make relation getting trust with clien social isolation very influence tosmoothness giving nursing care.